MODERN CONCEPTS OF NATIONAL SECURITY: A COMPARATIVE ANALYSIS OF THE US, EU AND UKRAINE MODELS - Krap, Andriy (Public Management and Policy, 2025)
The formation of the theoretical framework and the development of practical proposals for solving emerging risks, threats, and vulnerable situations for national security are actualized against the background of the conflict of Russia-Ukraine, geopolitical instability, and external pressure. The purpose of the study is a comparative analysis of modern concepts of national security of Ukraine, the European Community, and the United States in the context of current challenges of the present. The study found that Russia’s aggression in Ukraine has complicated global security problems, demanding an increase in the ability of state institutions to maintain a proper level of national security. It is established that the weak state security index for Ukraine reached critical values in 2023, actualizing the imperative of confrontation with external and internal threats. It is substantiated that the evolutionary national security landscape, characterized by increased instability and undergoing significant external pressure, requires careful revision in the context of functioning of the state security system of national security interests. The security concepts of the United States and the European Union in the aspects of successful practices of raising national security guarantees are analyzed. Empirical information analyzed in the article emphasizes the urgent need for effective strategic planning and integration of innovative operational framework to increase the level of national security of Ukraine. The results of the study emphasize the importance of the synergization of efforts and coordinated interaction between the countries of the global community, which experience similar threats to the protection of national sovereignty and territorial integrity, which is actualized against the background of the rapid dynamics of the geopolitical environment.